PELAKSANAAN PEMUNGUTAN PAJAK SARANG BURUNG WALET DI KECAMATAN LIMA PULUH OLEH DINAS PENDAPATAN DAERAH KOTA PEKANBARU - Mona Despita Ningsih; La Ode Syarfan (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
Local Tax is a source of local revenue in carrying out development which includes taxes of bird's nest, every entrepreneur swiftlet nests are required to pay tax in accordance with the Regulation of Urban Pekanbaru Number 10 Year 2011 on Swallow's Nest, in the District Fifty found 34 (thirty-four ) of bird's nest entrepreneurs who do not carry out the payment of taxes. executor of the tax collection of bird's nest is the Regional Revenue Office Pekanbaru. The purpose of this study was to examine the implementation of tax collection of bird's nest as well as to determine the obstacles in the implementation of tax collection of bird's nest. The method used in this research is descriptive survey with qualitative and quantitative approaches. based on the results of data analysis found that the tax collection of bird's nest as seen from the registration and data collection, determination, payment and billing quite accomplished